Flavokawain C Inhibits Cell Cycle and Promotes Apoptosis, Associated with Endoplasmic Reticulum Stress and Regulation of MAPKs and Akt Signaling Pathways in HCT 116 Human Colon Carcinoma Cells - Phang C.-W. (Public Library of Science (PLoS), 2018)
10.1371/journal.pone.0148775